Asal Usul dan Perkembangan Bani Uwaih - Azhar Saleh (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2010)
This article explains about BUwaihid Dynasty. First, it will explain about the root of the dynasty wich came from Dailam ethnic of Syirdil Awandan tribe lived in Jilan mountains, Iran. The founding of this dynasty were 3 brother, Ali, HAsan, and Ahmad (the second of Buwaih). Second, it will focus on the political achievements of the Buwaihid Dynasty wich are divided into jthree periods. Thhe first period(945-1012) was the time of power consolidation. THe second period (977-1012) was the time of ruling wich was started with Adhud al-Daulah's success in conquering Baghdad and continued with the ruling of his descendents. The third period (1012-1055) was the time of ruling wich was started with Adhud al-Daulah's success in conquering Baghdad and continued with the ruling of his descendents. The third period (1012-1055) was the time of the declining of the ruling started in 1012 until 1055 with al-Malik al-rahim as the last ruler. During Buwaihid Dynasty there was a changing of the ruler from chaliph palace (Dar al-Khilafah) to the kingdom palace (Dr al-Mamlakah) wich was built by the Buwaih dynasty in Baghdad.